Resepsi Hikayat Amir Hamzah Dalam Hikayat Umar Umayah - Kun Zachrun Istanti (Humaniora, 2008)
The receptive analysis on the texts responding to HAH show active responses from the readers by creating new texts, i.e HUU, Serat Ménak to contribute to the literary development in Nusantara. The relationship between HAH which is adapted into HUU is as followa. The Malay regard Umar Umayah’s character as cunning and humorous. His wit and humor in HAH is further exaggerated in HUU by being described not only as cunning and humorous Umar Umayah, other characters in HUU are ridiculed.